2016
DOI: 10.1245/s10434-016-5602-8
|View full text |Cite
|
Sign up to set email alerts
|

Surgeon Volume, Patient Age, and Tumor-Related Factors Influence the Need for Re-Excision After Breast-Conserving Surgery

Abstract: Re-excisions are frequent after BCS and are influenced by surgeon volume, patient age, and tumor-related factors. These factors should be considered when counseling patients considering BCS, and also for quality assurance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“… 10 17 25 27 32 33 Specialist breast cancer surgeons may be more proficient at obtaining negative margins, and less likely to re-excise close margins. 16 Patient selection and appropriateness of BCS as the initial treatment choice is also a factor. Anecdotal evidence suggests that treatment decisions made in high-volume hospitals are often made by multidisciplinary teams (MDTs) and differ from those made by clinicians working in isolation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“… 10 17 25 27 32 33 Specialist breast cancer surgeons may be more proficient at obtaining negative margins, and less likely to re-excise close margins. 16 Patient selection and appropriateness of BCS as the initial treatment choice is also a factor. Anecdotal evidence suggests that treatment decisions made in high-volume hospitals are often made by multidisciplinary teams (MDTs) and differ from those made by clinicians working in isolation.…”
Section: Discussionmentioning
confidence: 99%
“…Factors associated with reoperation can be broadly divided into patient-level sociodemographic and clinical factors, together with health system-level factors. 16 Comprehensive investigation into health system factors, which are potentially modifiable, is lacking, with few large population-based studies conducted, 8 10 11 17 only one of which 10 used best-practice multilevel modelling techniques to capture health system-level variation. If confirmed, variation in reoperation rates related to health system, rather than patient-level factors, has important policy and practice implications.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported reoperation rate and type of reoperation after BCS,115 but only a few focused on predictive factors determining reoperation type 11,13,16. We have analyzed institutional BC database in order to determine rates and associated factors for reoperation, mastectomy, and third reoperation.…”
Section: Introductionmentioning
confidence: 99%
“…Experience leads to compliance with recommendations on margins despite the surgical type of reconstruction and the location. This trend of better outcomes is noticeable for many surgeons in different types of surgery [ 25 , 26 ].…”
Section: Discussionmentioning
confidence: 98%